Paclitaxel, Iphospamide, and Cisplatin (TIP) as Bleomycin, Etoposide, and Cisplatin (BEP) Alternative for First-Line Therapy of Metastatic Germ Cell Tumor (GCT): A Case Series - Syamsu Hudaya; Adianti Khadijah (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Bleomycin, etoposide, and cisplatin (BEP) is a standard first-line therapy for metastatic germ cell tumor (GCT), while paclitaxel, ifosfamide, and cisplatin (TIP) are commonly used as salvage therapy after failed BEP treatment. The unavailability of first-line drugs can be the reason for the use of second-line therapy. In this paper, we reviewed two initial cases of patients with metastatic GCT treated with TIP as first-line chemotherapy in our center.Case Presentation: We reviewed the medical record and followed up two patients who had been treated with TIP as first-line chemotherapy for metastatic GCT due to lack of BEP regiment. We evaluated efficacy and toxicity of this treatment. These two patients were diagnosed with seminoma, with intermediate-risk according to International Germ Cell Cancer Collaborative Group (IGCCCG) classification. Both achieved complete response after four courses of TIP chemotherapy with toxicities mainly consisted of myelosuppression.Conclusions: TIP demonstrated efficacy serves as the first-line therapy for germ cell tumors with an acceptable safety profile. Further studies with larger subjects are still needed for evaluation. However, TIP is more expensive compared to BEP, making BEP is still superior to TIP in public hospital setting where cost-effectiveness of treatment is important.